Review of Ayurvedic concept of PCOS - Kumari, Suman; Saxena, Anjana (International Research Journal of Ayurveda & Yoga, 2021)
Introduction PCOS is very common chronic anovulatory disorder with androgen excess in women of reproductive age group. It is a multifactorial, multisystem disorder but obesity & insulin resistance are often associated. Patient present with symptoms of menstrual irregularities (either amenorrhea or oligomenorrhoea), androgen excess (hirsutism, acne alopecia) & USG evidences of >2-9 mm size arranged in the cortex of ovary. Aims To explore and understand ayurvedic pathogenesis of PCOS. Material and methods Classical Ayurvedic books, particularly the Charaka Samhita, were thoroughly examined, together with Sanskrit commentary, to compile a list of relevant references. A thorough search of the Internet was conducted to locate prior study papers and related material. Conclusion According to ayurvedic prospective it is studied and its pathogenesis is tried to be established. It can be considered as kapha vata predominant tridoshaja vikara & agnimandhya is main reason of pathogenesis. So, it can be effectively treated by tridosha pacifying, agnivardhak chikitsa with uttarvasti.